Stare.Js: An Extensible Open Source Toolkit for Visualizing Search Engine Results - Gonzalez-Ibanez, R; Gacitua-Vasquez, D (IEEE Computer Society, 2019)
Today, the leading presentation style of search engine results is a vertical list of text surrogates. Despite its wide adoption by search companies, this representation may not be suitable for all search tasks. Alternatively, visualizations can be used to create enriched surrogates of search results and at the same time exploit the advantages of human vision. Despite the potential benefits of visualizations, their implementation with current technologies either for research or actual applications can be complex and expensive. To tackle this problem, we introduce StArE.js, an extensible open source visualization package for Node.js to ease the process to implement and deploy visualization of search results. We demonstrate its effectiveness by contrasting the implementation of a visual representation of search results using Stare.js and a well-known visualization library. Our preliminary findings suggest that Stare.js can contribute to reduce the required effort to build visualizations of search results. © 2019 IEEE.